Study on the corrosion mechanism of the oxide scale on hot rolled steel in an atmospheric environment. Issue 5 (9th August 2019) - Cai, Jiaxing; Cheng, Xuequn; Zhao, Baijie; Chen, Linheng; Fan, Yi; Dai, Qinqin; Ma, Hongchi; Li, Xiaogang
Abstract : Purpose: The purpose of this paper is to understand the process of failure of scale and the corrosion resistance of scale to the substrate in an atmospheric environment. Design/methodology/approach: The corrosion behaviour of X65 pipeline steel with different types of oxide scale was analysed using the natural environment exposure corrosion test, scanning electron microscopy analysis, electrochemical corrosion polarization curve test and other methods in a warehouse environment. Findings: The results of this research show that one type of oxide scale, which is rough, has an uneven microstructure, and exhibits weak adhesion to the matrix, does not protect the substrate from corrosion. Conversely, the uniform, dense oxide scale, which exhibits strong adhesion to the matrix, provides effective protection to the steel. However, as the corrosion develops, the corrosion rate of the substrate tends to accelerate, especially when the structure of the oxide scale is damaged to a certain extent. Originality/value: The corrosion mechanism of the oxide scale on hot rolled steel in an atmospheric environment has been proposed.